1965
DOI: 10.1113/jphysiol.1965.sp007616
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gravity on gastric emptying with various test meals

Abstract: The rates at which the gastric contents are usually passed into the duodenum are much less than the maximal rate which the stomach can achieve. The rates are submaximal because the propulsive mechanism of the stomach is usually partly inhibited through the excitation of duodenal receptors responding to the duodenal contents, recently transferred from the stomach. This being so, mechanical hindrance to the gastric propulsive mechanism might be expected to have little influence on the usual rate of gastric empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Our current observations and those reported previously [1,2,4] can be explained by the interplay of propulsive forces generated by intragastric volume/gravity with inhibitory feedback arising from the small intestine. The overall gastric emptying of nutrients, such as glucose, is known to be highly regulated, so that caloric loads to the duodenum remain relatively constant over a wide range of intragastric concentrations [31][32][33]; the extent of small intestinal feedback is dependent on the length of the small intestine exposed to nutrient [34,35].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Our current observations and those reported previously [1,2,4] can be explained by the interplay of propulsive forces generated by intragastric volume/gravity with inhibitory feedback arising from the small intestine. The overall gastric emptying of nutrients, such as glucose, is known to be highly regulated, so that caloric loads to the duodenum remain relatively constant over a wide range of intragastric concentrations [31][32][33]; the extent of small intestinal feedback is dependent on the length of the small intestine exposed to nutrient [34,35].…”
Section: Discussionmentioning
confidence: 48%
“…These observations add significantly to existing information about the effects of posture/gravity on gastric emptying. Gravity has been shown to influence gastric emptying of lownutrient liquids, so that emptying is substantially faster in the erect than the supine position [1,2,4], as well as to modify he intragastric distribution [4]. In contrast, posture has been reported to have no effect on overall emptying of highnutrient liquids, measured by intubation techniques [1,2] or scintigraphy [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the trial cited above, BurnMurdoch et al did not find any significant influence of posture on the emptying rate of 750 ml of a glucose drink. Despite the force of gravity being the same for both kinds of liquids, corresponding studies confirmed this difference [6,7]. Whereas intragastric volume and gravity appear to be the driving forces controlling gastric emptying of nonnutrient liquids [2,5,8], for nutrient liquids, feedback from small intestinal "nutrient" receptors is the decisive factor.…”
Section: Effects Of Posture On the Gastric Residence Time Of Fluids Amentioning
confidence: 56%
“…This can explain the lower antral speed detected in our controls compared to that referred by the authors in the presurgical assessment [1,2]. In this regard, we would like to warn the authors about the use of water that could produce a drawback in quantitative assessment due to influence of posture and gravity for liquids in gastric emptying [3,4]; furthermore, steady-state imaging with a semisolid homogeneous food (like pudding) could be more achievable for gastric function evaluation, because of the marked contrast between stomach and neighboring structures produced by this kind of food [5]. Another limitation, in our opinion, concerns the need to evaluate the reproducibility of data extrapolation from imaging over all for antral speed assessment.…”
mentioning
confidence: 70%